Dampak Kelebihan Kapasitas terhadap Pemenuhan Hak-Hak Warga Binaan di Lembaga Pemasyarakatan Kelas IIA Jember - Aldiena Qodar, Isl; Supianto, Supianto; Wahyuningtyas, Yuli Winiari (WELFARE STATE Jurnal Hukum, 2022)
Overcapacity of detainees occurs in almost all prisons, this excess capacity causes various problems in prisons, such as the failure of the main purpose of the prison, namely the development of Correctional Assisted Citizens (WBP) and can lead to new crimes due to the excess capacity. The excess capacity of the inmates will have an impact on the fulfillment of the rights that should be obtained by the inmates. The aim of this research is to find out the impact of excess capacity of inmates on the fulfillment of the rights of inmates in the Class IIA Jember Penitentiary. This research uses normative and empirical research methods. The results showed that the impact of the excess capacity of inmates in the Class IIA Jember Penitentiary, among others: the difficulty of the prisoners to rest and activities, disruption of the rights of inmates, inadequate sanitation, conflicts that cause fights, and less than optimal supervision by officers. In an effort to overcome the impact of excess capacity of WBP, Jember Prison carries out various preventive and repressive efforts.